Biofloc as a potential natural feed for shrimp postlarvae - Azizah, Endut; Helena, Khatoon; Sanjoy, Banerjee (Elsevier Ltd, 2016)
In this study, the suitability of excess biofloc that was discarded as waste from Litopenaeus vannamei farm effluent was investigated for effectiveness as a dietary replacement in rearing L. vannamei postlarvae (PL). A commercial shrimp diet (control) was compared to four diets containing dried waste biofloc at 25%, 50%, 75% and 100% replacement levels and fed to shrimp PL to evaluate the survival rate, growth performance and nutritional composition. Total ammonium nitrogen and nitrite nitrogen were maintained in culture tanks with minimal water exchange throughout the experiment. Results showed that PLs fed with 50% biofloc feed (50% BF) had significantly higher (p < 0.05) specific growth rate compared to the other treatments. In addition, PLs fed with 50% and 75% BF had significantly higher survival rate (p < 0.05) compared to those fed with commercial feed only. However, protein content of PLs fed with 50% and 75% BF was comparable to those of 100% commercial feed. This study demonstrates that waste biofloc has potential to be used as a cost effective feed for rearing shrimp PLs.